Economic correlates of suicide rates in OECD countries - Thomas Maag (ETH Zurich, KOF Swiss Economic Institute, 2008)
This paper investigates how economic conditions are associated with age-sex group specific suicide rates in a panel of 28 OECD countries over the period 1980-2002. We consider the trend and cyclical components of income, unemployment, income inequality, inflation, as well as various socio-demographic control variables. Results depend on whether stationarity properties are adequately accommodated or not. Estimating models in first differences we find that the cyclical component of income is negatively associated with suicide rates of men, while unemployment primarily affects suicide rates of women. Moreover, our estimations show that the effects of the cyclical component of income and unemployment are most pronounced in OECD countries with low public social security spending.
Keywords: D60; H51; I10; 330; suicide; happiness; welfare; health; Soziale Lage; Selbstmord; Zufriedenheit; Soziale Sicherung; OECD-Staaten